Back Cover: Targeting the Substrate Binding Site of E. coli Nitrile Reductase QueF by Modeling, Substrate and Enzyme Engineering (Chem. Eur. J. 22/2013). Issue 22 (17th May 2013) - Wilding, Birgit; Winkler, Margit; Petschacher, Barbara; Kratzer, Regina; Egger, Sigrid; Steinkellner, Georg; Lyskowski, Andrzej; Nidetzky, Bernd; Gruber, Karl; Klempier, Norbert
<x xml:space="preserve">Abstract</x> Nitrile reductase QueF catalyzes the reduction of a nitrile to its corresponding amine. In their Full Paper on page 7007 ff., N. Klempier et al. report on the investigation of active‐site binding and the substrate scope of E. coli QueF by modeling, enzyme, and substrate engineering. The active‐site residues and structural features of the substrates essential for catalysis were identified in spectrophotometric and HPLC‐MS based screenings of active‐site mutants and natural substrate analogues.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>